Assessment of Physical-Chemical Characteristics of Water and Sediments from a Brazilian Tropical Estuary: Status and Environmental Implications - Madson de G. Pereira; Marta V. A. S. de Andrade; Vanessa C. Ornelas; Raimunda A. N. de Almeida; Maurício P. F. Fontes; Joselito N. Ribeiro; Araceli V. F. N. Ribeiro; Arnaud V. dos Santos; Adriana N. Souza; Claudiane B. de Araújo; Ana C. B. de Araújo; Cássia R. E. Onofre; et al. (The Scientific World Journal)
The environmental quality of the Jacuípe River's estuary (very important in northeastern Brazil) was assessed during 2007 and 2008. In water, concentrations (mg L−1) of NO2- (<0.004 to 0.016), NO3- (0.01 to 0.33), soluble PO43- (<0.02 to 0.22), dissolved oxygen (3.9 to 9.6), total contents (mg L−1) of Cd (<0.001), Cu (<0.01), Pb (<0.01), and Zn (<0.1), pH (5.60 to 8.00), and electrical conductivity (0.12 to 48.60 mS cm−1) agreed with environmental standards. In sediments, clay and total organic matter (%, m/m) varied, respectively, from 8.8 to 12.0 and from 1.1 to 8.8, while infrared, thermogravimetric profile, electronic micrograph, as well as X-Ray analyses showed desirable adsorptive characteristics. However, maximum exchangeable levels (mg kg−1) of Cd (1.3), Cu (44.6), Pb (35.7), and Zn (43.7) and their respective maximum pseudototal concentrations (mg kg−1): 19.4, 95.1, 68.2, and 30.3 were below the recommended limits. In this sense, it was possible to demonstrate good environmental preservation even with the growing number of industries and touristic activities in the evaluated estuarine area.